Incentive bargaining and corporate governance : comparative enterprise law among the US, Japan, and China / Zenichi Shishido, Wei Shen. - Shishido, Zen'ichi, 1956-; Shen, Wei, 1972- (Cambridge University Press, 2026)
This comparative analysis of business systems examines firms and enterprises across three major economies in the world: the US, China and Japan. It asks how the law relates to business practice, economic growth and social development; and how enterprise law maximizes firm value in these three jurisdictions. The divergent legal, social and economic approaches towards the market, firms, and business and corporate law in these three major economies justify a close scrutiny of enterprise law with the aim of better understanding legal and economic models for social and economic development in a comparative context. This book will be of interest to academics and practitioners in law, business, management, public policy, political science, and economics. It offers a useful framework for legislative policy makers across the world - particularly in developing countries.